Victor Borge classic collection. [Disc] 1, The best of Victor Borge. Acts one & two [videorecording (DVD)] - Borge, Victor (Distributed by Questar, 2008)
This is classically funny music as only legendary international entertainer Victor Borge, "the comedian of the keyboard," can perform it. Borge has made generations laugh with his timeless routines and dazzling musicianship."--Container.